A review of fire mitigation methods for li‐ion battery energy storage system. Issue 3 (11th May 2022) - Sebastian, Roshan
Abstract: Lithium‐ion battery (LIB) carries an inherent risk of thermal runaway (TR), which may result in off‐gassing (flammable, toxic, or explosive), fires, and explosion. This article focuses on various fire protection approaches to mitigate LIB fires in a battery storage energy system (BESS). As BESS has its own unique battery chemistry, with different arrangements of battery modules and facility‐specific emergency response strategies, a case‐by‐case approach is vital to design fire protection for large‐scale LIB‐based BESS. This third article in a six‐part series is a review of fire mitigation methods for Li‐ion BESS.